PARTISIPASI MASYARAKAT DALAM PERENCANAAN DAN IMPLEMENTASI PROGRAM PEMBANGUNAN DESA DI KAMPUNG MESYAM DISTRIK AIFAT TIMUR JAUH - SYAMA, SILVESTER (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT :This study departed from the indication of a problem that is still low community participation in rural development Mesyam village / town . Therefore the aim of this study to answer the question " how community participation in the planning and implementation of development programs in Kampung District Mesyam Aifat Maybrat Far East District of West PapuaThe method used is descriptive method .. Sources of data / research respondents were as many as 40 people consisting of government officials villages , officials BPD / BAPERKAM , LPM and PKK officials , leaders / community leaders , and citizens generally Kampung Mesyam . Collecting data using questionnaires and assisted with interviewing techniques . The analysis technique used is descriptive analysis .Based on these results conclusions drawn : ( 1 ) Participation in the Village community Mesyam village planning / villages are generally low , (2 ) public participation in the process of Kampung Mesyam implementation / execution of development programs rural / village , it is good enough / high but generally still limited to the forms of labor participation .Starting from the conclusion of the study it is necessary to recommend the following suggestions : ( 1 ) It takes more effort to move or improve effective community participation in the planning Mesyam Kampung village development , (2 ) participation in Mesyam Village community in the implementation process or the execution of the program - rural development programs also need to be upgraded or expanded , which is not only limited to the form of force participation but also in the form of donations in accordance with the ability of the material it self.